2006
DOI: 10.2987/8756-971x(2006)22[666:afeofl]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Field Evaluation of Four Larval Mosquito Control Methods in Urban Catch Basins

Abstract: Effective control of mosquitoes in rural Midwestern communities that lack organized mosquito control districts would be aided by baseline data on optimal breeding sites, interannual effects of climate on population emergence and abundance, and efficacy of various control options under field conditions. During 19 surveillance weeks in the summer of 2005, we sampled 100 catch basins each week that were distributed among 10 study zones. Catch basins within each study zone were subjected to 1 of 4 different mosqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…As suspected, catch basins in parking areas were surrounded by more impervious surface and fewer trees, similar to the characteristics of the "high-density urban areas" described by Kronenwetter-Koepel et al (2005) and Stockwell et al (2006). And, similar to those previous studies, parking area sites held catch basins that produced mosquitoes at a rate of 30% or less than that of residential street catch basins which were surrounded by less impervious surface and more trees.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…As suspected, catch basins in parking areas were surrounded by more impervious surface and fewer trees, similar to the characteristics of the "high-density urban areas" described by Kronenwetter-Koepel et al (2005) and Stockwell et al (2006). And, similar to those previous studies, parking area sites held catch basins that produced mosquitoes at a rate of 30% or less than that of residential street catch basins which were surrounded by less impervious surface and more trees.…”
Section: Discussionsupporting
confidence: 84%
“…The following year and in the same study area, Stockwell et al (2006) observed that 50 catch basins sampled weekly in similarly-named "highintensity" urban areas (<20% of land area covered in vegetation) held a little more than a third of the mosquitoes found in 50 basins in "low-intensity" urban areas (areas mixed with impervious surfaces and vegetation). Those authors suggested that a factor in these observed differences may have been the volume of organic debris captured in basin sumps.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations